Analysis of Community Participation in the Decision-Making Process of the Bulukumba Regency Regional Government - Andi Fitrah Rezkyah Ramadhani Fahrin; Herman H; Rifdan; Andi Anugrah Mahyuddin (Universitas Negeri Makassar, 2026)
This study aims to analyze and describe community participation in local government decision-making using the empowerment theory developed by Julian Rappaport. The analysis emphasizes four principal dimensions: the forms and levels of community participation, the implementation of empowerment principles, particularly influence and control, the supporting and inhibiting factors affecting participation, and the effectiveness of participatory policies in promoting inclusive and sustainable local development. This research employs a descriptive qualitative approach. Data were collected through observation, documentation, and in-depth interviews with six purposively selected informants, consisting of village technical supervisory officials, legislative members, community leaders, and grassroots residents in Kecamatan Gantarang. The findings indicate that community participation is predominantly procedural and formalistic, often influenced by nationally driven development agendas rather than locally initiated priorities. The empowerment principle has not been fully achieved due to limited community control, which is strongly influenced by village fiscal dependency on government transfers. Structural barriers also restrict participation, including limited human resource capacity, local elite domination, and inadequate public access to policy information. Participatory policies are considered administratively effective in facilitating public involvement but have not generated transformative outcomes in strengthening community empowerment. This study concludes that participation remains at a consultative level and requires revitalization through digital transparency, strengthened village autonomy, and regulatory harmonization based on local wisdom. Such efforts are essential to support inclusive, participatory, and sustainable local governance outcomes in the future context.